Measurement of the Polarization Characteristics of Coherent Diffraction Radiation in the Subterahertz Range; JETP Letters; Vol. 109, iss. 12 - Shkitov D. A. Dmitriy Andreevich; Potylitsyn A. P. Alexander Petrovich; Naumenko G. A. Gennadiy Andreevich; Shevelev M. V. Mihail Viktorovich; Aryshev A.; Terunuma N. Nobihiro; Urakawa J. Junji (2019, 2019)
Title screen